Establishment Of Village Regulations In Realize Autonomy Village - Roy Marthen Moonti (Susbtantive Justice International Journal of Law, 2018)
Provision of regional autonomy is the granting of authority and flexibility to regions to manage and utilize regional resources optimally, of course, the granting of such authority must be balanced with the establishment of adequate regulations. However, there are still many problems related to the formulation of regulations, especially the village regulations. As long as government-cooled development starts from the lowest levels of government, the village has not proceeded as desired. The purpose of this study to determine the Status of Village Rules In Autonomy Village Governance System. The research method used in the preparation of this research is the normative juridical method that is in answering the problem used the legal point of view based on the applicable law regulation, to then be connected with the reality in the field related to the issues to be discussed. Village regulations serve as indicators in the successful implementation of village autonomy. In Law Number 6 Year 2014 Article 115 letter b and e jo Article 112 paragraph 1 stipulates the provision that the Regency / Municipal Government shall supervise and administer the Village Government which in the case of Village Regulation in the form of guiding the formulation of Village Regulation and Village Head Regulation as well as evaluating and supervision of Village Rules.